2020
DOI: 10.1111/cen.14373
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ambulatory blood pressure between patients with primary aldosteronism and other forms of hypertension

Abstract: Objective Primary aldosteronism (PA) is a potentially curable cause of hypertension associated with worse cardiovascular prognosis than blood pressure‐matched essential hypertension (EH). Effective targeted treatment for PA is available with the greatest benefit seen if treatment is started early, prior to the development of end‐organ damage. However, PA is currently substantially under‐diagnosed. The standard screening test for PA, the aldosterone‐to‐renin ratio (ARR), is performed infrequently in both primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Precise hemodynamic status and blood pressure pheno-type determination at baseline does not allow us to distinguish primary aldosteronism subtypes from our current data. These results are in coherence with previous smaller studies, which do not find any significant difference between BP phenotype and primary aldosteronism subtypes even with essential hypertension [27][28][29].…”
Section: Discussionsupporting
confidence: 92%
“…Precise hemodynamic status and blood pressure pheno-type determination at baseline does not allow us to distinguish primary aldosteronism subtypes from our current data. These results are in coherence with previous smaller studies, which do not find any significant difference between BP phenotype and primary aldosteronism subtypes even with essential hypertension [27][28][29].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a relatively large sample study also demonstrated that nocturnal BP decline was lower in PA than in EH, whereas only patients with idiopathic hyperaldosteronism (IHA) had higher nighttime BP than those with EH [23]. However, previous studies have not analyzed BP load variation in patients with PA. Only a few studies have reported that patients with PA have a higher overall BP and BP load than patients with EH, despite no difference in dipping status [24]. Our data are the rst to suggest that the new indicator of nighttime SBP TIR is closely related to composite CVD events in patients with PA, whereas clinic BP, 24-hour SBP or DBP, daytime SBP or DBP, nighttime SBP or DBP, BP decline, daytime SBP or DBP TIR, and nighttime DBP TIR are not signi cantly related to those in patients with PA. Additionally, there were no signi cant differences in aldosteronism between patients with PA with and without composite CVD events.…”
Section: Discussionmentioning
confidence: 99%
“…Libianto et al reported that patients with PA had higher overall BP and BP load than patients with essential hypertension, despite no differences in nocturnal dipping or BP variability during 24-hour monitoring [9]. Furthermore, information on the relationship between the different ABPM hypertension phenotypes and cardiovascular complications in patients with PA is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Further confounding diagnosis, primary aldosteronism can present like essential hypertension14: blood pressure can be anywhere from pre-hypertension (120-130/80-89 mm Hg) to resistant hypertension (resistant to three conventional antihypertensive drugs) 15. Hypokalaemia, once thought to be an essential feature of primary aldosteronism, is now found to be present in only a minority of patients (box 1).…”
Section: Why Is It Missed?mentioning
confidence: 99%